Море - Костылев Валентин Иванович (Золотая летопись России, 1992)
Экземпляры: аб (20210827) / Инвентарный номер: 57392 / Цена: 30.00 / Сис.шифр: Р2 / Авт.знак: К72 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6